Synthesis and Studies of Potential Antifungal and Antibacterial Agents New Aryl Thiazolyl Mercury (II) Derivatives Compounds - Abolfath Akbarzadeh; Reza Soleymani; Milad Taheri; Halimeh Rajabzadeh; Mehdi Daryani (Journal of Chemistry, 2013)
Combination of mercaptothiazoles and mercury phenyl chloride synthesized some new compounds of thiazoles. Firstly some mercaptothiazoles with different sorts have been synthesized, and then synthesized compounds were reacted with different mercury phenyl chloride structures. At last, each of these synthesized compounds was purified. Consequently, these structures were recrystallized using oil ether. Forming product through chromatogram (TLC) and combination of Rf with other compound's Rf of were identified, and their purity percent was recognized. The 1H-NMR and other methods like FT-IR and mass spectroscopy have determined all of compounds. Obtained results of synthesized compounds showed that reactions were carried out with suitable speed and high yield.